Research on toothbrush trees leading to the social, environmental and business ideas / Ibtisam Abdul Wahab, Hannis Fadzillah Mohsin and Ayla Farihah Ibrahim - Abdul Wahab, Ibtisam; Mohsin, Hannis Fadzillah; Ibrahim, Ayla Farihah (Universiti Teknologi MARA Shah Alam, 2020)
Salvadora or the toothbrush tree (miswak) originates from Pakistan, India, South Africa and West Asian countries. The fibrous branch is packed in a pen-shaped holder, as an innovative form and marketed internationally. This prophetic and endangered, medicinal plant genus is promoted by the World Health Organization. The extracts are now extensively used in dentistry. The products are manufactured in pharmaceutical and cosmetics industries, as the toothpaste, tooth gel and mouth rinse. In this study, a literature search on Salvadora is conducted. Both miswak articles and products are available online. The journals on Salvadora were systematically reviewed. Here, a parallel update of this natural resource, plus its business and entrepreneurship, are presented. A clinical trial was performed to investigate the effect of mouth wash, extracted from S. persica on dental plaque formation. The antiplaque efficacy of the miswak mouth rinse, in comparison to that of chlorhexidine, was recently published. Meanwhile, the chemistry of S. oleoides was studied. A number of molecules were isolated from various parts of the plant, including the leaves, seeds, stems and roots. They consist of salvadorin; a dimeric dihydroisocoumarin, phytosterols e.g. beta-sitosterol and its glucosides, fatty acids, essential oils, salvadoricine; an indole and the sulfur-containing organic substance, known as salvadoside. Nevertheless, artifacts could be produced, following the alcoholic extraction of Salvadora species. Attempts on the synthesis of analogues of Salvadora alkaloid were also made. It is anticipated that more research could be carried out for the economic benefit of this plant.